Multipurpose conjugated block copolymers based on novel triphenylylamine derivatives and squaric acid for electrochromic and resistive memory devices. (January 2020) - Bai, Ju; Zhang, Yaxin; Dong, Liyan; Hou, Yanjun; Niu, HaiJun; Wang, Shuhong; Wang, Cheng
Abstract: Here, we synthesized two kinds of novel conjugated block copolymers P1 and P2 by reacting squaric acid and three kinds of homemade diamine monomers. The polymers P1 and P2 can be dissolved in many normal organic solvents and form films by solution-cast method with high mechanical properties. In addition, when the 10% weight loss is selected as a reference point, the polymers P1 and P2 showed the thermal decomposition temperatures at around 309 and 312 °C, respectively. The polymer films exhibit high coloration efficiencies (CE) (262–282 cm 2 C −1 ) and good cyclic stabilities. In addition, the ITO/polymer/Al sandwich memory devices exhibited non-volatile resistive switching behaviors with low write, erase voltages (more than −0.6 V and less than 3.1 V, respectively), good ON/OFF ratio (843 and 1435) and reliable cycling endurance (more than 30, 000 cycles). These properties illustrate that the polymers could be considered as potential electrode materials for both electrochromic and resistive memory devices. Highlights: Two kinds soluble high coloration efficiency electrochromic polymers based squaric acid and three kinds diamines were synthetised. The polymers showed good solubility in organic solvents and good film forming capability, and exhibit high thermal stability. The films of the polymers showed high electrochromic coloration efficiency (CE) and electrochromic stability. Non-volatile resistive switching behaviors with low write, erase voltages, good ON/OFF ratio, reliable cycling endurance. Potential electrode materials for both electrochromic and resistive memory devices.